2011 IEEE Global Telecommunications Conference - GLOBECOM 2011 2011
DOI: 10.1109/glocom.2011.6133706
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Channel Access in Cognitive Radio Networks Based on Variable Order Markov Models

Abstract: The concept of Cognitive radio enables the unlicensed users to share the spectrum with licensed users, on the condition that the licensed users have preemptive priority. The use of the channel by unlicensed users should not result in more than acceptable interference level to the licensed users, if interference occurs. The sense and react strategy by unlicensed users sometimes does not lead to acceptable level of interference while maintaining an acceptable data transfer rate for the unlicensed users.Proactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Introducing one more state named ''fuzzy'' (unknown availability), a 3-state higher-order HMM channel state predictor is introduced in [17]. Instead of using a fixed length of observations, a variable order Markov model is introduced in [18]. Recently, a frequent pattern mining (FPM) based predictor [5] demonstrates that it provides better channel state prediction performance over the first-order HMM-based predictor.…”
Section: Related Workmentioning
confidence: 99%
“…Introducing one more state named ''fuzzy'' (unknown availability), a 3-state higher-order HMM channel state predictor is introduced in [17]. Instead of using a fixed length of observations, a variable order Markov model is introduced in [18]. Recently, a frequent pattern mining (FPM) based predictor [5] demonstrates that it provides better channel state prediction performance over the first-order HMM-based predictor.…”
Section: Related Workmentioning
confidence: 99%
“…The continuous demand for wireless communication technologies and systems Wireless Engineering and Technology has reached a peak where existing capacity cannot meet increasing demand without means of improving the efficiency of spectrum utilization. The Owned spectrum allocation policy also known as the fixed spectrum allocation policy has led to Spectrum Scarcity [1] [2] [3]. However, research by Federal Communications Commission (FCC) Spectrum Policy Task Force showed that a large portion of the assigned spectrum was used sporadically, leading to under-utilization of a significant amount of spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there are mainly three categories of PSA schemes as follows: analytic formulations ( [9][10][11]), heuristic schemes based on assumed channel usage ( [12][13][14][15]), and heuristic schemes based on channel usage learning ( [4,[16][17][18]). Most of the learning methods like neural networks (e.g., [16]) and binary time series models (e.g., [18]) in the literature fixed the value of the memory to be used in prediction.…”
Section: Existing Schemes On Psamentioning
confidence: 99%
“…In Sections 1.3 and 1.2, we discuss some available solutions for the problems 2 and 5, respectively. This paper is an extension to the work in [4]. In that paper, we only discussed the usage of probabilistic suffix tree (PST) as a prediction mechanism, where there was only a single SU trying to access the channel.…”
Section: Introductionmentioning
confidence: 99%